Designing â€œBreast Self Examinationâ€ Application For Detecting Breast Cancer As Effort For Women Ages 15-20 Years - Diana Aqidatun Nisa (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2020)
Breast cancer is the second dangerous disease for women after cervical cancer in the world. In 2012, it became the most disease suffered by women in Indonesia. Ministry of health records in 2013 that the patient of breast cancer is increasing for women from the age group between 15-20 years old. Health institutions have been doing education campaigns about preventive action against this disease to young women. However, the feeling of embarrassment, fear, and overconfidence of being healthy would have prevented them from reviewing their breast condition checked by medical doctors or specialists. Their lack of awareness about the diseaseâ€™s danger has made them checked regularly, neither review their breast to the doctor nor do a self-examination. The education about breast cancer is vital to gain awareness of young women. It should be delivered by the media that close to them, for instance, using smartphone technology. Breast cancer information via smartphone can summarize much information; besides, it is easy to access privately anywhere, anytime. It can be delivered in an instructive, brief, yet still interactive and easy to learn without being boring. The smartphone application called â€œSAATNYA SADARIâ€ design is based on qualitative research. The method is carried out by studying the literature, questionnairing among young women between 15-20 years old, interviewing the specialist, and surveying the Hospital and Indonesian Cancer Foundation. BSE is focused on the early detection of breast cancer and self-examination education so that the women can do it as a routine.